P435 The impact of perianal fistula in Crohn's disease on quality of life: results of a patient survey conducted in Europe. (27th May 2021) - Spinelli, A; Yanai, H; Lönnfors, S; Girardi, P; Milicevic, S; Carvello, M; Maroli, A; Avedano, L
Abstract: Background: Perianal fistulas (PAF) in Crohn's disease (CD) may impair social performance, sexual function, life activities and overall patients' quality of life (QoL). Patient experience is important in the treatment decision making and in providing adequate support. Despite the clinical relevance, few studies have addressed the patient perspective on the impact of PAF and complex PAF (CPAF) in CD on QoL. Methods: A questionnaire assessing the impact of PAF on QoL was developed by patient representatives and medical experts addressing diagnosis, symptoms and QoL including close relationships, social life, sexual activity and working life. CD patients with and without PAF were invited to participate. The self-selective anonymous survey was available in 11 languages and accessible on the European Federation of Crohn's & Ulcerative Colitis Associations' (EFCCA) website and national inflammatory bowel disease patient association websites from 15 July to 31 December 2019. Results: Of 820 respondents with CD (67.2% women; mean age 40.8 years), 532 (64.9%) reported PAF in CD of which 272 (51.1%) reported CPAF. PAF/CPAF patients had experienced and were currently experiencing more anal pain and perianal leaking than CD patients (Figure). On a 10-point scale, PAF/CPAF patients reported a greater impact on overall QoL (6.91 vs 6.18, p<0.001), relationships with family and friends (5.54 vs 4.78, p<0.001), relationship with partner (5.24 vs 4.11, p<0.001), social life (5.65 vs 4.97, p=0.001) and working life (5.54 vs 5.12, p=0.02) than CD patients. PAF/CPAF patients reported feeling more unhygienic, uncomfortable, and guilty about their condition toward family and friends than CD patients. They also found it more difficult to talk with family and close friends about their condition. PAF/CPAF patients avoided having sex, ended relationships, had arguments with partner, felt inadequate to partner, avoided dating and had their partner refuse having sex more often than CD patients. Furthermore, these patients were unable to play sports, carried a personal hygiene kit, were aware of access to clean toilets, and had changed profession/career due to their condition more often (Figure). Conclusion: From the patients' perspective, PAF/CPAF in CD severely impacts patients' overall QoL, social and sexual relationships and work life. These results are important to consider when tailoring treatment strategy and patient services in a multidisciplinary way to address individual patient needs.